Montreal cognitive assessment as a cognitive outcome measure in progressive supranuclear palsy - Vanessa Ibrahim; Catherine Isroff; Christopher D. Stephen; Jay Iyer; Marian L. Dale; Douglas A. Gunzler; Ece Bayram; Tao Xie; Alex Pantelyat; Leila Montaser-Kouhsari; Indira Garcia-Cordero; Indira Garcia-Cordero; et al. (Frontiers in Neurology)
BackgroundThe Montreal Cognitive assessment (MoCA) is a well-validated global cognitive screening instrument. Its validity in progressive supranuclear palsy (PSP) has not been assessed.ObjectivesTo evaluate the MoCA as an outcome measure in PSP clinical trials.MethodsCognitive data from 162 participants in the placebo arm of the Biogen PASSPORT study (NCT03068468) were analyzed using linear mixed-effects modeling (LMM) and repeated measures correlation.ResultsThere was a significant decline in the MoCA score over time of −1.4 (95% CI −0.84 to −1.97) points over a 48-week period (p < 0.0001). Small but significant changes (p < 0.01) were observed in all MoCA domains except abstraction. The MoCA correlated weakly with the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) over time (rrm = 0.1, p = 0.02) but exhibited a stronger correlation with the PSP Rating Scale (PSPRS) (rrm = −0.25, p < 0.0001).ConclusionThe MoCA appears to have limited sensitivity in capturing cognitive decline in PSP.